STRATEGI GURU DALAM PENGEMBANGAN PSIKIS ANAK AKIBAT PENGARUH GAME ONLINE (Studi Kasus di Raudlatul Athfal Dewi Mashitoh Gunungjati Jabung) - Baiti Firdausah; Anwar Sa’dullah; Mutiara Sari Dewi (Jurnal Dewantara, 2021)
The purpose of this study is to describe (1) the psychological development of children who are addicted to playing online games at RA Dewi Mashitoh Gunungjati Jabung, (2) the teacher's strategy to develop psychic children who are addicted to playing online games at RA Dewi Mashitoh Gunungjati Jabung, and (3) supporting factors obstacles in developing children's psychology at RA Dewi Mashitoh Gunungjati Jabung. This study uses a qualitative method with a descriptive approach. This research was conducted at RA Dewi Masithoh Gunungjati Jabung in May 2020. The research data were obtained by interviewing, observing, and documenting techniques. The results showed that (1) In RA. Dewi Mashitoh, found several children who experienced psychological problems due to addiction to playing online games. There are three children, namely one girl and two boys. The forms of psychological disorders experienced are language problems, disturbances in the emotional and behavioral aspects, and the tendency to do unfavorable behavior. (2) Psychic development strategies applied by teachers in RA. Dewi Mashitoh is implementing art therapy, namely by allowing children to do drawing, painting, sculpture, and other artistic activities. (3) Supporting factors in the psychological development of children who are disturbed by addiction to playing online games are support from foundations and parents, learning tools and media that are always available, and additional incentives for teachers. While the inhibiting factors faced are technical obstacles and lack of cooperative behavior from students, demanding tasks that are quite heavy for teachers, and teacher intrapersonal problems.